Servant Leadership and Innovative Work Behavior in Chinese High-Tech Firms: A Moderated Mediation Model of Meaningful Work and Job Autonomy - Cai, Wenjing; Lysova, Evgenia I.; Khapova, Svetlana N.; Bossink, Bart A. G. (Frontiers in Psychology, 2018)
While scholars acknowledge the critical role of employee innovative work behavior (IWB) in facilitating organizational innovation in the high-tech industry, current knowledge is far from complete to specifically paint a clear picture of how to evoke employee IWB in Chinese high-tech industry sectors. Drawing on a dynamic componential model of creativity and innovation, this study proposes and tests a moderated mediation model that examines the positive influence of servant leadership on employee IWB via meaningful work as well as the moderating role of job autonomy in this process. We collected data (N=288) from three Chinese high-tech firms and found that employees’ perceptions of meaningful work mediate the relationship between servant leaders and IWB. We also found that this mediating relationship is conditional to the moderating role of job autonomy in the path from servant leadership to meaningful work. The results further show that the indirect effect of servant leadership on employee IWB via meaningful work exists only when job autonomy is high.